Characterization and identification of two economically important WHITEFLY SPECIES, GENUS Aleurodicus, SUBFAMILY ALEURODICINAE (HEMIPTERA: ALEYRODIDAE) from Western Java, Indonesia - Purnama Hidayat,; Lia Nurulalia,; Sari Nurulita,; Dhango, Vincentius H. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Two whitefly species belong to the genus Aleurodicus, subfamily Aleurodicinae (Hemiptera: Aleyrodidae), have been reported to attack various hosts in Indonesia. Identification of the subfamily Aleurodicinae based on the morphological character has been described in previous studies. However, there was a limitation on identification based on morphological character. In addition, the genetic information of those species collected from Indonesia is still little known. Therefore, this study aimed to characterize and identify two whiteflies of the subfamily Aleurodicinae collected from several districts in the Western Java, Indonesia area using morphology and genetic characteristics. The samples from Ancol (District of North Jakarta) and Cipanas (District of West Java) were used for molecular identification. First, the morphological character was determined based on pupa and adult profiles. The molecular identification was conducted using primer pair C1-J-2195 and L2-N-3014 that covered partly the COI region. The colony of whiteflies from Ancol and Cipanas was identified as Aleurodicus disperses and A. dugesii, respectively. Partial COI sequence analysis showed that A. disperses Ancol has a similarity of more than 99-100% and grouping with other A. disperses species from Asia. Meanwhile, the partial COI sequence of A. dugesii Cipanas shared more than 99% similarity with A. dugesii from the USA.